1967
DOI: 10.1152/ajplegacy.1967.213.5.1233
|View full text |Cite
|
Sign up to set email alerts
|

Albumin multiplier in kidney vasa recta analyzed by microspectrophotometry of T-1824

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…3) suggests that colloid oncotic pressure may have been lower in the peritubular capillaries of the BUL rats than in the controls. Although arterial plasma protein concentrations were not measured, there was no significant difference in arterial hematocrits between the BUL and control rats (42.8 ±1.3% vs. 44.0 ±2.1%) suggesting that no major change had occurred in intravascular volume in the BUL animals. Decreased colloid oncotic pressure has been shown to reduce net sodium reabsorption, at least in the proximal tubule (62).…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…3) suggests that colloid oncotic pressure may have been lower in the peritubular capillaries of the BUL rats than in the controls. Although arterial plasma protein concentrations were not measured, there was no significant difference in arterial hematocrits between the BUL and control rats (42.8 ±1.3% vs. 44.0 ±2.1%) suggesting that no major change had occurred in intravascular volume in the BUL animals. Decreased colloid oncotic pressure has been shown to reduce net sodium reabsorption, at least in the proximal tubule (62).…”
Section: Methodsmentioning
confidence: 85%
“…In the normal medulla, the hypertonic environment probably causes blood viscosity to rise due to the crenation of red cells (41) and the threefold increase in protein concentration that occurs in the vasa recta (42)(43)(44)(45)(46). Therefore, medullary hypertonicity may determine, in part, the efferent resistance of the juxtamedullary glomneruli.…”
Section: Methodsmentioning
confidence: 99%
“…Those investigations suggested the existence ofa large extravascular pool ofalbumin in the renal medulla. Injection ofalbumin labeled with various markers including radioiodine (3), FITC (4,5), and Evans blue dye (5,6) supported the presence of interstitial albumin. Histochemical methods have been used to examine the pathway by which macromolecules gain access to the interstitium.…”
Section: Introductionmentioning
confidence: 97%
“…A possible connection between extravascular albumin and the urine concentrating process has been described by Pinter [19] who found a significant correlation between the urine osmolality and the extravascular albumin distribution space in the canine medulla, but no explanation for this finding was apparent. Wilde and Vorburger [33] discussed the interaction between the accumulation of extravascular albumin by means of an ‘albumin multiplier’ and the entry of Na into the inner medullary interstitium. MacPhee [16] concluded that both HA and extravasated albumin were involved in the inner medullary concentrating process, but the mechanism of this effect was not specified.…”
Section: Discussionmentioning
confidence: 99%